The effect of tax planning, company value, and leverage on income smoothing practices in companies listed on Jakarta Islamic Index - Novia Megarani; Warno Warno; Muchammad Fauzi (Journal of Islamic Accounting and Finance Research, 2019)
Purpose - The purpose of this paper is to identify the effect of tax planning, company value, and leverage on income smoothing practice in companies listed on the Jakarta Islamic Index for the period 2010-2017.